2023
DOI: 10.1002/anie.202218252
|View full text |Cite
|
Sign up to set email alerts
|

Ionothermal Synthesis of Metal‐Organic Frameworks Using Low‐Melting Metal Salt Precursors**

Abstract: Metal-organic frameworks (MOFs) are porous, crystalline materials constructed from organic linkers and inorganic nodes with myriad potential applications in chemical separations, catalysis, and drug delivery. A major barrier to the application of MOFs is their poor scalability, as most frameworks are prepared under highly dilute solvothermal conditions using toxic organic solvents. Herein, we demonstrate that combining a range of linkers with low-melting metal halide (hydrate) salts leads directly to high-qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…139 Our group has shown that ionothermal synthesis using lowmelting metal salt precursors provides access to a wide range of acid-stable MOFs by simply combining metal salts and organic linkers together at high temperatures. 140 Intriguingly, frameworks produced using this method possess crystallinity and porosity comparable to those synthesized under traditional dilute solvothermal conditions.…”
Section: Robustness Of Mofs For Organic Synthesismentioning
confidence: 88%
“…139 Our group has shown that ionothermal synthesis using lowmelting metal salt precursors provides access to a wide range of acid-stable MOFs by simply combining metal salts and organic linkers together at high temperatures. 140 Intriguingly, frameworks produced using this method possess crystallinity and porosity comparable to those synthesized under traditional dilute solvothermal conditions.…”
Section: Robustness Of Mofs For Organic Synthesismentioning
confidence: 88%
“…For example, ionothermal synthesis enables the preparation of porous materials without the need for organic solvents . Our group has shown that ionothermal synthesis using low-melting metal salt precursors provides access to a wide range of acid-stable MOFs by simply combining metal salts and organic linkers together at high temperatures . Intriguingly, frameworks produced using this method possess crystallinity and porosity comparable to those of frameworks synthesized under traditional dilute solvothermal conditions.…”
Section: User-friendly Mof Synthesismentioning
confidence: 99%
“…47 Encouraged by this finding, we sought to prepare azolate and salicylate MOFs�materials that are especially promising for catalysis but are limited by dilute (<0.01 M) synthesis conditions and long (>7 days) reaction times�without solvent, utilizing low-melting molten metal (hydrate) salts as ionothermal media (Figure 5). 48 Starting with azolate MOFs, we identified the open-metal site M 2 Cl 2 (btdd) (M = V, Mn, Fe, Co, Ni, Cu) family of MOFs as promising candidates for ionothermal synthesis. 8 Indeed, combining the corresponding metal chloride hydrate salts with the H 2 btdd linker at temperatures above the melting point of the salt (160 °C), yields Co 2 Cl 2 (btdd) and Ni 2 Cl 2 (btdd) after 16 h. Notably, the temperatures at which these reactions are performed is below the melting or decomposition points of the corresponding linkers.…”
Section: Ionothermal Synthesismentioning
confidence: 99%
“…Starting with azolate MOFs, we identified the open-metal site M 2 Cl 2 (btdd) (M = V, Mn, Fe, Co, Ni, Cu) family of MOFs as promising candidates for ionothermal synthesis . Indeed, combining the corresponding metal chloride hydrate salts with the H 2 btdd linker at temperatures above the melting point of the salt (160 °C), yields Co 2 Cl 2 (btdd) and Ni 2 Cl 2 (btdd) after 16 h. Notably, the temperatures at which these reactions are performed is below the melting or decomposition points of the corresponding linkers . These samples can be purified from soluble impurities via Soxhlet extraction.…”
Section: Ionothermal Synthesismentioning
confidence: 99%